Менеджмент дистанційної роботи в умовах пандемії - Ковшик, Валентин Ігорович; Яценко, Ольга Миколаївна; Горбунов, Микола Петрович (Видавничий дім "Інтернаука", 2021)
Майже два роки людство живе в умовах пандемії, пов’язаної з коронавірусною хворобою і пройшло шлях від повного нерозуміння стосовно того, що робити і як жити й працювати далі, до етапу, коли вже приймаються зважені і продумані рішення і розробляються програми виходу з кризи. Викликом для багатьох став новий формат дистанційної роботи, до якого не були готові ні керівники, ні підлеглі. У статті розглянуто значення терміну «дистанційна робота», кількість «дистанційних працівників» у світі до часів пандемії, особливості законодавчого регулювання дистанційної праці в Україні та кількість людей, що мали змогу працювати вдома після запровадження карантину в державі.

For almost two years, humankind has been living in a coronavirus pandemic. It has gone from a complete misunderstanding of what to do and how to live and work to a step where informed and thoughtful decisions are already being made, and crisis management programs are being developed. The challenge for many was a new format of remote work, for which neither managers nor their subordinates were ready. The article considers the meaning of the term “telework” (“remote work”), the number of remote workers in the world before the pandemic, the peculiarities of the legal regulation of telework in Ukraine, and the number of people who were able to work from home after the introduction of quarantine in the country. The problems in management that complicate the transition to the remote format of work are analyzed. Authors list industries with a high and medium ability to work remotely; describe psychological aspects of unpreparedness for the transition to remote employment of managers and subordinates. Emphasis is placed on the availability of certain technical capabilities, as well as special knowledge, skills, and abilities to master tools for remote work, which highlights the need for continuous training of staff. It is noted that the classic management functions have also transformed: they take into account the prevention and leveling of the impact of negative factors associated with the pandemic. The key directions of managerial and organizational work during the pandemic are substantiated: ensuring the safety of workers, providing staff training, providing technical capabilities for remote work, and implementation of management functions. The general methodical approach and recommendations concerning the system of organizational measures having three structural blocks are presented: the general organizational measures; ensuring the safety of participants in bureaucratic procedures that require personal contact; providing technical capabilities for remote work. It is assumed that if the proposed measures are applied, enterprises and organizations will be able to increase their efficiency, operate in a crisis, and reduce the negative impact of the pandemic on workers.
Remote work management during a pandemic
Keywords: дистанційна робота; віддалена робота; організація праці; управління; менеджмент; пандемія; COVID-19; remote work; telework; labor organization; management; pandemic